Comorbid Psychopathology and Alcohol Use Patterns among Methadone Maintenance Treatment Patients. (23rd March 2015) - Moussas, Georgios; Fanouraki, Irene; Pachi, Argiro; Asomatou, Arezina; Drylli, Olga; Paschalakis, Georgios; Tselebis, Athanasios; Giotakis, Konstantinos; Bratis, Dionisios; Dermatis, Georgios; Malliori, Meni
Abstract : 130 patients from a methadone maintenance treatment program agreed to complete Symptoms Checklist 90-Revised (SCL-90R) and Alcohol Use Disorders Identification Test (AUDIT) self-report scales. Scores higher than the proposed cut-score on SCL-90R scale were observed on depression, obsessions-compulsions, paranoid ideation, anxiety, anger-hostility, somatization, interpersonal sensitivity, and psychoticism subscales. In sum, 42.9% of our sample exhibited depressive symptomatology, 34.9% obsessive-compulsive symptoms, 29.1% somatization, 27.2% anxiety symptoms, 22.2% paranoid ideation, 19% phobic anxiety, 15.1% psychoticism, and 15.1% hostility and 11.9% presented with symptoms of interpersonal sensitivity. Mean score on AUDIT scale was6.9 ± 7.9 . 63.0% of our participants scored below cut-off and were classified as having a low level of alcohol-related problems; 24.4% scored in the range of 8–15 which is an indication of alcohol abuse whereas 12.6% scored 16 and above indicative of serious abuse/addiction. Scores on AUDIT scale were positively correlated with length of time on methadone treatment, but not with length of time on drug use or age of our participants. Positive correlations were observed among AUDIT and SCL-90R scores, namely, with global severity index score, positive symptom distress index, positive symptom total, and all primary symptom dimensions subscales except phobic anxiety.